Constructing students' deontic status by use of alternative recognitionals for student reference. Issue 2 (4th May 2018) - Ishino, Mika; Okada, Yusuke
Abstract: Since student participation is essential for successful classroom teaching, a growing number of studies are investigating how classroom teachers can encourage active participation by students. In line with the prior findings on participation management practices, this study reports on three English language teachers' student participation management practice of addressing students with a particular referential formulation (e.g. 'fool', 'expert in chemistry'), which we will define as 'alternative recognitionals' against 'default student reference forms' (e.g. 'Mister X', 'Miss Y'). The data comprised 15 h of video recordings in English-as-a-foreign-language (EFL) classrooms at a junior high school, a senior high school and a university in Japan. Using a conversation-analytic framework, we explicate the teachers' use of alternative recognitionals at certain moments in classroom interaction. The analysis revealed that the particular lexical choice of student reference form constructed the referent student's particular deontic status at a certain moment of classroom institutional interaction. The constructed deontic status then made it relevant for the teacher to initiate or elicit a particular action (e.g. sharing special knowledge, delivering/receiving punishment) in relation to the referent student. Thus, the teachers used constructed deontic status as a resource for the management of student participation in ongoing classroom activity.